Energy‑safety balanced composites of attractive cyclic nitramines with polyaniline - Patil, Veerabhadragouda B.; Machalický, Oldřich; Bělina, Petr; Svoboda, Roman; Trzcinski, Waldemar A.; Zeman, Svatopluk (My University, 2024)
Composite microcrystals of the cyclic nitramines 2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane (ε-CL-20), 1,3,5-trinitro-1,3,5-triazinane(RDX), 1,3,5,7-tetranitro-1,3,5,7-tetrazocane (β-HMX), and cis-1,3,4,6-tetranitrooctahydroimidazo-[4,5-d]imidazole (BCHMX) with polyaniline (PANi) have been prepared and thoroughly characterized in terms of morphology and phase purity. PANi outperformed other conducting polymers in terms of selectivity towards NAs due to its better interaction with NAs, low production cost, and ease of preparation. The bonding of nitramines with the polymeric PANi chain has been examined by means of Fourier transform infrared (FTIR), Raman spectroscopy methods, and fuorescence quenching; the Raman spectrum has shown the laser sensitivity of these microcrystals. Powder X-ray difraction results have shown changes in polymorph modifcations in CL20 (from ɛ to β) and HMX (from β to α) during the preparation of the composites, which have also been confrmed by spectral and diferential thermal analysis techniques. The structural orientations found in these composites signifcantly stabilize nitramines against impact; their detonation properties have slightly deteriorated, but the PANi electrical conductivity has strongly increased their electric-spark sensitivity. The above properties of the prepared composites determine their potential use mainly as parts of the electric or laser impulse initiators, having “a green character”, for various charges.
Energeticky vyvážené kompozity atraktivních cyklických nitraminů s polyanilinem
Keywords: Polyaniline; Nitramines; PANi-composites; Impact sensitivity; Electric-spark Sensitivity; Polyanilin; nitraminy; PANi-kompozity; citlivost na náraz; citlivost na elektrickou jiskru